2013
DOI: 10.1002/aqc.2338
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of central Mediterranean stocks of the loggerhead turtle (Caretta caretta) using mitochondrial and nuclear markers, and conservation implications

Abstract: In migratory species female- and male-mediated gene flow are important for defining relevant Management Units, and for evaluating connectivity between these and their respective foraging grounds. The stock composition at five Mediterranean foraging areas was investigated by analysing variation in the mitochondrial D-loop and six microsatellite loci in a sample of 268 loggerhead turtles (Caretta caretta) stranded or accidentally caught by fisheries. This involved a comprehensive Mixed Stock Analysis which consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 69 publications
(114 reference statements)
2
28
0
Order By: Relevance
“…Analysing genetic differences can therefore provide information on the relative contribution of different rookeries to a common foraging ground, rather than on the origin of a single individual (e.g. for the Mediterranean: Carreras et al 2006;Garofalo et al 2013).…”
Section: Methods For Studying Sea Turtle Movementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysing genetic differences can therefore provide information on the relative contribution of different rookeries to a common foraging ground, rather than on the origin of a single individual (e.g. for the Mediterranean: Carreras et al 2006;Garofalo et al 2013).…”
Section: Methods For Studying Sea Turtle Movementsmentioning
confidence: 99%
“…Genetic studies too have indicated high proportions of Atlantic individuals in the oceanic zone of the Sicily Channel (Laurent et al 1998) as well as their occurrence in the neritic zone of the Tunisian continental shelf (Figure 5), though at a lower proportion (Casale et al 2008b). Current data suggests that Atlantic turtles do not enter the Adriatic or do so in very low numbers (Giovannotti et al 2010;Garofalo et al 2013). The occurrence of Atlantic loggerheads in other parts of the eastern Mediterranean basin is possible but has not yet been adequately assessed through genetic surveys.…”
Section: Atlantic Loggerheads In the Mediterraneanmentioning
confidence: 99%
“…1). The northern Adriatic is an important foraging area for adults from Greek (Lazar et al 2004, Carreras et al 2006, Giovannotti et al 2010, Garofalo et al 2013 and Turkish rookeries, as well as for juveniles (Casale et al 2004). Other important areas are the southern Adriatic (Casale et al 2012a), the Ionian Sea, the Strait of Sicily, and the Tunisian shelf (Margaritoulis et al 2003, Casale et al 2007b, Casale et al 2014).…”
Section: Sea Turtle Distributionmentioning
confidence: 99%
“…Other important areas are the southern Adriatic (Casale et al 2012a), the Ionian Sea, the Strait of Sicily, and the Tunisian shelf (Margaritoulis et al 2003, Casale et al 2007b, Casale et al 2014). The latter is frequented by turtles from Greek rookeries, Libya, and the Atlantic (Garofalo et al 2013).…”
Section: Sea Turtle Distributionmentioning
confidence: 99%
See 1 more Smart Citation